Effect of bimetallic NiW modified crystalline ZSM‐5 zeolite on catalytic conversion of crude palm oil and identification of biofuel products. Issue 1 (27th November 2016) - Subsadsana, Maliwan; Sangdara, Pakpoom; Ruangviriyachai, Chalerm
Abstract: In this study, the catalytic performance of bimetallic NiW modified ZSM‐5 catalysts for hydrocracking conversion of crude palm oil is presented. Crystalline ZSM‐5 zeolites with precisely controlled SiO2 /Al2 O3 ratios (SARs) of 30, 50, 70 and 100 were successfully synthesized from kaolin via the hydrothermal method. To enhance their catalytic activity, as‐prepared zeolites were modified with Ni, W and NiW by the impregnation technique. The catalysts were characterized by various techniques. The total amount of Ni and W in the catalysts was determined by inductively coupled plasma atomic emission spectroscopy technique and found to be in the range of 3.08–3.16 and 5.88–6.39 wt%, respectively. These NiW‐ZSM‐5 catalysts showed good activity for the production of biofuels, and their catalytic activity decreased in the order NiW‐ZSM‐5 > Ni‐ZSM‐5 > W‐ZSM‐5 > ZSM‐5. The incorporation of NiW improved the production of both hydrogenation and dehydrogenation hydrocarbon compounds. Moreover, the different SARs in ZSM‐5 zeolite also affected the catalytic activity and NiW‐ZSM‐5 with SAR of 50 gave an excellent conversion (96.20%). Additionally, the types of the obtained hydrocarbon products were identified as gasoline (C5 –C10 ), kerosene (C9 –C11 ) and diesel (C10 –C20 ) by simulated distillation gas chromatography‐flame ionization detector and gas chromatography–mass spectrometry. © 2016 Curtin University of Technology and John Wiley & Sons, Ltd. © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.